Ex Vivo Evaluation of Bacterial Leakage and Coronal Sealing Capacity of Six Materials in Endodontically Treated Teeth - Paiva, Salma Mota da Silva; Fontana, Carlos Eduardo; Rocha, Daniel Guimaraes Pedro; Martin , Alexandre Sigrist De; Delboni, Maraisa Greggio; Bueno, Carlos Eduardo Da Silveira (Iranian Endodontic Journal, 2022)
Introduction: Successful endodontic treatment requires an effective coronal sealing to prevent the penetration of saliva and microorganisms into the root canal system. We aimed to investigate the sealing capacity of Maxxion R, Intermediate Restorative Material (IRM), Mineral Trioxide Aggregate-like material (Biodentine), White Cimpat, Flow Resin and Z250 Resin against Enterococcus (E.) faecalis infiltrates, when used as coronal sealants after endodontic treatment. Materials and Methods: Sixty-six roots of adult lower premolars were randomly divided into 6 experimental groups with 10 roots each (n=10), and two control groups (positive and negative) with three roots each. The root canals were instrumented to ProTaper F3 file, irrigated with 2.5% NaOCl and 17% EDTA, and filled using Tagger’s Hybrid technique with AH-Plus cement. After removing 2 mm of the coronal third filling with a Gates Glidden #6 drill, the cervical portion of each of the sixty roots was sealed with a 2 mm-thick plug, plus the respective material being tested in this study. All roots were fitted to silicone devices (Eppendorf) with cut extremities and sterilized with ethylene oxide; experimental procedures were performed in a laminar flow chamber for aseptic chain maintenance. All specimens were inoculated with E. faecalis, and the culture medium was renewed every 3 days for 60 days. Medium turbidity was evaluated daily. The obtained data were subsequently submitted to analysis of variance (ANOVA-R) complemented by Student’s t-test at a significance level of 5%. Analyzes of variance were calculated using the SAS system GLIMMIX procedure. Results: Biodentine (56.90), Z250 Resin (54.90) and White Cimpat (53.30) resisted contamination for a longer time compared to Maxxion R (51.30), Flow Resin (50.70), and IRM (48.70) over a period of 60 days. Conclusion: Biodentine, Resin Z 250 and White Cimpat presented the lowest infiltration averages when compared to the other tested materials.